Simulation of a shock absorber with vertical buckling tubes welded in the longitudinal direction. (January 2015) - Dundulis, Romualdas; Kilikevičius, Sigitas; Krasauskas, Povilas; Dundulis, Gintautas; Rimkevičius, Sigitas
Highlights: A special shock absorber design for nuclear engineering is presented. Tubes welded in the longitudinal direction were used to absorb the impact energy. The mechanical properties of the tube steel and its welded joint were examined. The influence of the weld was investigated by numerical simulation. The longitudinal weld does not influence a noticeable adverse effect. Abstract: The Ignalina Nuclear Power Plant (NPP) has two RBMK-1500 graphite moderate boiling water multi-channel reactors. The Ignalina NPP Unit 1 was shut down at the end of 2004 while the Unit 2 was shut down at the end of 2009. Spent fuel assemblies are located in the pools of Ignalina NPP Units. These spent fuel assemblies will be loaded to the special casks for storage of the spent fuel assemblies. The drop of the cask during the lifting and lowering operation has to be taken into account as an unlikely event. Shock absorbers are mounted on the bottom of the stepped pool. A special shock absorber design using vertical buckling tubes has been developed. In case of a drop of the cask, the buckling tubes dissipate the kinetic and potential energy and reduce the impact force to the floor. These tubes are made of a stainless steel sheet and welded in the longitudinal direction. Therefore, the influence of the weld on vertical buckling of the tubes should be evaluated. Finite element analysis software ABAQUS was used to estimate the influence of the weld on the plastic deformation behaviour of the tubes.